Catalytic reduction of 4-nitrophenol and methylene blue by biogenic gold nanoparticles synthesized using Carpobrotus edulis fruit (sour fig) extract. (8th June 2022) - Madiehe, Abram M; Moabelo, Koena L; Modise, Keletso; Sibuyi, Nicole RS; Meyer, Samantha; Dube, Admire; Onani, Martin O; Meyer, Mervin
Along with the increasing requirement for efficient organic conversions using green chemistry, there is a need to develop highly efficient and eco-friendly catalytic reaction systems. Gold nanoparticles (AuNPs)-based nanocatalysts are promising candidates for the reduction of environmental pollutants, such as nitroaromatics and dyes. This study reports on the green synthesis of AuNPs using Carpobrotus edulis (C. edulis) fruit aqueous extract (CeFE) and their catalytic activities. The CeFE induced rapid reduction of gold (III) salt to form monodispersed and spherical AuNPs, with a core and hydrodynamic sizes of 40 and 108.7 nm, respectively. CeFE alone had no effect on 4-nitrophenol, whereas incubation with methylene blue (MB) caused reduction of the peak at 665 nm. Addition of CeFE-AuNPs in the presence of NaBH4, caused the reduction of 4-nitrophenol to 4-AP, and MB to leucoMB within 10 min. These reactions followed the pseudo first-order kinetics. Therefore, biogenic CeFE-AuNPs could be used for the elimination of noxious environmental pollutants.